Civil society organizations as a vital support for persons with disability in Croatia - Urbanc, Kristina (Socialno delo, 2014)
The paper provides some information about the development of civil society associations for persons with disabilities in the post-war community in the process of social reconstruction. The Republic of Croatia, as a signatory to the UN Convention on the Rights of Persons with Disabilities took over the role of improving the situation of persons with disabilities in society. However, the current crisis of Croatian society has particularly harmed people with disabilities and their families, as well as their position in society and their participation in everyday life. Beside the state's resources, which are more and more diminished, constant support for people with disabilities from NGOs is becoming a vital resource for their participation in everyday life. This paper presents the work of a few local NGOs engaged in disability activism in the context of a specific evolution of the civil society in Croatia.
Keywords: civilnodružbene organizacije; hendikep; osebe z ovirami; človekove pravice; human rights; Hrvaška; Croatia